PENGARUH ADMINISTRASI PENDIDIKAN,PENGAWASAN TERHADAP MUTU PROSES BELAJAR MENGAJAR DI RAUDHATUL ATFHAL (RA) KAB GOWA - Abdul Rahman Abdi (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
This research in order to identify and analyze: 1) the influence of administration education on the quality of learning and teaching proces. 2) The effect of head school controlling to the quality of learning and teaching proces, and 3) Effect of simultaneous adminstration education and head school controlling to the quality of learning an teaching proces in Gowa regency. This study used Instrument data collectors in the form of questionnaires to all teachers RA Gowa regency. Population of 76 all primary teachers RA gowa regency with a sample of 76 people teachers. The sample in this study using saturated sampling technique and statistical analysis was used to test the hypothesis is multiple linear regression analysis the results showed that there are contribution independent variables (adminstration education influence on the variable quality of laerning and teaching proces in Gowa (-2,971,666). The results showed that there are contribution independent variables (head school controlling) influence on the variable quality of laerning and teaching proces in Gowa (6,421 1,666). Variable administration education and head school controlling simultaneously affect the quality of learning and teaching proces in Gowa 61,0% percent. have a significant influence independent variable on the variable quality of learning and teaching proces Gowa regency in value 0,000 < 0,05.